The Institute for Global Orthopedics and Traumatology: A Model for Academic Collaboration in Orthopedic Surgery - Conway, Devin James; Coughlin, Richard; Caldwell, Amber; Shearer, David (Frontiers in Public Health, 2017)
In 2006, surgeons at the University of California, San Francisco (UCSF) established the Institute for Global Orthopedics and Traumatology (IGOT), an initiative within the department of orthopedic surgery. The principal aim of IGOT is to create long-term, sustainable solutions to the growing burden of musculoskeletal injury in low- and middle-income countries (LMICs) through academic partnership. IGOT currently has relationships with teaching hospitals in Ghana, Malawi, Tanzania, Nicaragua, and Nepal. The organizational structure of IGOT is built on four pillars: Global Surgical Education (GSE), Global Knowledge Exchange (GKE), Global Research Initiative (GRI), and Global Leadership and Advocacy. GSE focuses on increasing surgical knowledge and technical proficiency through hands-on educational courses. The GKE facilitates the mutual exchange of surgeons and trainees among IGOT and its partners. This includes a global resident elective that allows UCSF residents to complete an international rotation at one of IGOT’s partner sites. The GRI strives to build research capacity and sponsor high-quality clinical research projects that address questions relevant to local partners. The fourth pillar, Global Leadership and Advocacy aims to increase awareness of the global impact of musculoskeletal injury through national and international courses and events, such as the Bay Area Global Health Film Festival. At the core of each tenet is the collaboration among IGOT and its international partners. Over the last decade, IGOT has experienced tremendous growth and maturation in its partnership model based on cumulative experience and the needs of its partners.